(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
The rapid development of Industry 5.0 emphasizes the need for effective communication between humans and robotic systems, particularly mobile robots operating in dynamic environments. Traditional data transmission methods face challenges related to latency, security, and adaptability, necessitating new approaches to ensure seamless information exchange.